GenAI as a cognitive mediator: a critical-constructivist inquiry into computational thinking in pre-university education - Sánchez Muñoz, Jonathan Arturo; Flores-Eraña, G.; Silva-Campos, Juan Manuel; Chavira-Quintero, Rigoberto; Olais-Govea, José Manuel (Frontiers in Education, 2025)
This qualitative study investigates how high school students engage with generative artificial intelligence (GenAI), particularly ChatGPT, and how this interaction influences computational thinking and knowledge construction. Guided by a critical-constructivist framework, the research employed an action-research methodology structured around design thinking, prompt engineering, Python programming, and elevator pitch activities. Content analysis was conducted to trace the evolution of students’ cognitive strategies, with particular attention to how they formulated effective prompts, assessed and refined AI-generated responses, and iterated on their problem-solving approaches. Results show that while GenAI fosters creativity and computational fluency, it simultaneously raises challenges related to epistemic vigilance, critical reflection, and project feasibility. The study concludes that pedagogically grounded integration of GenAI requires balancing automation with the cultivation of analytical, ethical, and metacognitive capacities. These findings contribute to ongoing debates on AI-enhanced education by emphasizing the importance of structured and reflexive pedagogies to foster critical digital literacy and epistemic agency at the secondary level.